Corporate volunteering, positive relationships at work, affective commitment, and work engagement: A mediated moderator model - FU, Yusheng (Journal of Positive Management, 2022)
Purpose: The aim of this study is to test for moderating role of corporate volunteering in relationships between perceived supervisor support, positive relationships at work, work meaningfulness, and work engagement. Methodology/approach: The study is based on a survey conducted on a sample of 724 Polish employees, both involved and non-involved in corporate volunteering. Findings: Results of the study suggest that employee participation in corporate volunteering moderates the link between positive relationships at work and work engagement, and the link between perceived supervisor support and work engagement mediated by positive relationships at work. Implications: Results of the study are consistent with previous studies, which have been proved theoretically by the conservation of resources theory (COR) and self determination theory (SDT). Besides, the findings deliver practical implications. Companies are recommended to design employee-friendly volunteering activities to meet employee needs, and attract those employees who have never participated in volunteering. Originality/value: The study explains the effects of corporate volunteering. It also contributes to the field of organizational behaviors by arguing for the direct and indirect positive relationships between perceived supervisor support and work engagement. Keywords: corporate volunteering, affective commitment, work engagement, positive relationships at work Paper type: Research paper